Means of unitary operators, revisited - Haagerup, Uffe; Kadison, Richard V.; Pedersen, Gert K. (MATHEMATICA SCANDINAVICA, 2007)
It is proved that an operator with bound not exceeding (n-2)n^-1 in a C^*-algebra is the mean of n unitay operators in that algebra.